Non-target risk assessment of Cotesia typhae, a potential biological control agent of the Mediterranean corn borer - Taiadjana M. Fortuna; Loïc Colin-Duchevet; Yanna Desreumaux; Rémi Jeannette; Manuel Le Gonnidec; Bruno Le Ru; Romane Mettauer; Florence Mougel; Laure Kaiser (Biological Control)
Biocontrol of exotic insect pests can be achieved by introducing natural enemies from the native range. This method has been successful in controlling many pests worldwide, but negative effects on local non-targets have sometimes occurred. Before the introduction of exotic macro-organisms useful for crop protection, a risk assessment is mandatory under EU regulations. In this study, we assessed the non-target risks of the larval parasitoid Cotesia typhae (Hymenoptera, Braconidae), a potential agent for inundative biocontrol of the Mediterranean corn borer Sesamia nonagrioides (Lepidoptera, Noctuidae), both natives to Sub-Saharan Africa. The effects of C. typhae on 8 non-target species was determined by sequential analysis under laboratory conditions, including tests of acceptance, development monitoring, olfactory attractiveness and in planta parasitism test. The results varied considerably between species. By multiplying the probability of outcome of the successive steps of the parasitism process, we estimated that non-target species had lower average risks of C. typhae development (1 % of non-target larvae at risk) and of induced mortality (5 %) compared to S. nonagrioides larvae (41 and 42 % respectively). The highest mortality risk in planta was observed for the cattail stemborer, Nonagria typhae (9 %), although it was still lower than for the target species (33 %). These host range results and the low survival capacity of the parasitoid at winter temperatures, suggest a low long-term environmental risk, which is supported by the estimation of the global risk index proposed by van Lenteren et al. (2003). The host range and impact of C. typhae in field conditions will soon be determined.